Eastern Bloodsucking Conenose, Triatoma sanguisuga (LeConte) (Hemiptera: Reduviidae: Triatominae) - John L. Capinera (EDIS, 2013)
The eastern bloodsucking conenose belongs to the subfamily Triatominae, known as the kissing bugs. Despite their affectionate vernacular name, they are particularly threatening “assassin bugs” who require blood meals to survive and reproduce. They are a known vector of American trypanosomiasis (or Chagas Disease) in South America, a debilitating illness caused by the parasite Trypanosoma cruzi. This disease is a problem in South and Central America and has been detected in the United States, but has not been found in Florida. This 4-page fact sheet was written by John L. Capinera, and published by the UF Department of Entomology and Nematology, November 2013. http://edis.ifas.ufl.edu/in1018